Boosting Employee Performance: The Impact of Career Development and Competitive Compensation - Pratamtomo, Gunthur Bayu; Kasbuntoro, Kasbuntoro; Prabantoro, Gatot (Research of Business and Management, 2024)
This research aims to find out how much influence work discipline and providing incentives have on employee performance at PT. TOA Galva Industries Department Speaker 1. The population in this study was speaker section 1 at PT. TOA Galva Industries Department Speaker 1. totaling 83 people. The research methods used in this research are regression, correlation, determination, t-test, r-test, and F-test. The research results show that both career development and compensation have a significant influence on employee performance. Effective career development can improve employee skills and motivation, while fair and competitive compensation can increase employee satisfaction and loyalty. The combination of these two factors contributes positively to increasing employee performance. This research provides practical implications for organizational management in designing effective career development strategies and compensation policies to improve employee performance and achieve organizational goals. Ite managerial implication of these findings is that company management needs to pay attention to and develop effective career development programs and provide a fair and competitive compensation system. In this way, companies can improve overall employee performance, which will ultimately contribute to achieving organizational goals